Mencari Definisi Kehadiran Antar-Subjek yang Bermakna di Ruang Digital - Binsar Jonathan Pakpahan (Institut Agama Kristen Negeri Toraja, 2021)
We need to re-define what is presence, especially in the frequent use of digital rooms and encounters during the Covid-19 pandemic. The article argues that meaningful presence in the digital rooms could be understood through Martin Heidegger idea in the metaphysics of presence and and Jacques Derrida's critique on it. Heidegger states that Dasein must think and analyze his or her thrownness in the world presence, so the presence is not an accidental event. Dasein also builds a relationship with other Dasein. Meanwhile, through the critique of the metaphysics of presence Derrida helps us to understand the signs and traces of presence that comes to us in his discussion on speech and text. By constructing an imagined discussion between both philosophers in the context of our question, the article will build an argument that meaningful presence between subjects can be achieved in the digital space. AbstrakDalam penggunaan pertemuan di ruang digital yang menjadi salah satu mode pertemuan di masa pandemi Covid-19, kita perlu memberi definisi ulang mengenai apa itu kehadiran. Makalah ini akan berargumen bahwa kehadiran yang bermakna di ruang digital bisa dipahami melalui lensa berpikir metaphysics of presence yang diajukan oleh Martin Heidegger dan Jacques Derrida. Heidegger mengatakan bahwa kehadiran tidak boleh menjadi sebuah proses yang tidak sengaja dan harus menjadi relasi yang membuat Dasein (subjek) menyadari keterlemparannya dalam ruang dan waktu. Derrida akan membuat kita menyadari akan tanda dan jejak kehadiran yang datang kepada kita dalam pembahasannya mengenai speech (ucapan) dan text (teks). Melalui kombinasi pemikiran keduanya, tulisan ini menunjukkan bahwa kehadiran antar-subjek yang bermakna bisa dicapai dalam ruang digital.